Zoom to the moon! - Pat-a-Cake; Uno, Kat (London Pat a cake, 2019)
Zoom to the Moon introduces big ideas to little ones! This first book about space will delight young babies. With shiny foil to focus on and bright colour to capture and keep their attention, this book will be revisited time and time again - and also be interesting to older toddlers. The shiny foil and big touch-and-feel patches make this book a perfect present
A sparkly space book
Scientific Notions
Shiny book
Keywords: Science